Nutritional Status among Adolescents at SMK IBU Jember: Implications for School-Based Obesity Prevention Programs - Wike Rosalini (Journal of Nursing Periodic, 2026)
Abstract Introduction: Nutritional status is a key determinant of adolescents’ health and academic performance, while recent national and provincial data indicate a rising prevalence of overweight and obesity among Indonesian youth, including in East Java and Jember Regency. This study aimed to describe the distribution of nutritional status among students at SMK IBU Jember Regency as a basis for school-based nutrition promotion and prevention of non-communicable diseases. Methods: A descriptive cross-sectional study was conducted among 93 students measured on 18 February 2026, using BMI categories (underweight, normal, overweight, obesity) and descriptive analysis with frequencies and percentages. Results: Of the students, 5.4% were underweight, 62.4% had normal nutritional status, 29.0% were overweight, and 3.2% were obese, so 37.6% experienced nutritional problems, with 32.2% having excess body weight Conclusions: The high proportion of overweight and obesity compared with underweight indicates a growing problem of excess body weight among adolescents and underscores the need for school-based and community-supported interventions to promote healthy eating and physical activity